2005
DOI: 10.1002/jso.20257
|View full text |Cite
|
Sign up to set email alerts
|

Expression of L-type amino acid transporter 1 (LAT1) in esophageal carcinoma

Abstract: These results suggest that LAT1 plays a significant role in cell proliferation, differentiation, and invasion in esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 10 publications
4
73
0
2
Order By: Relevance
“…Kobayashi et al (48) described that LAT1 expression in esophageal carcinoma was higher in cancerous tissue than in noncancerous tissue, and the expression increased in relation to depth of invasion, maximum tumor diameter, and differentiation. In our study, LAT1 expression did not increase in connection with pleural involvement, lymphatic permeation, vascular invasion, or lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al (48) described that LAT1 expression in esophageal carcinoma was higher in cancerous tissue than in noncancerous tissue, and the expression increased in relation to depth of invasion, maximum tumor diameter, and differentiation. In our study, LAT1 expression did not increase in connection with pleural involvement, lymphatic permeation, vascular invasion, or lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LAT1 is often excessively expressed in primary human neoplasms of various organs and is involved in tumor cell proliferation due to its function in transporting essential amino acids (4)(5)(6). Previous studies have demonstrated the upregulation of LAT1 immunohistochemically in prostate cancers (7), as well as in squamous cell carcinomas (8,9), gliomas (10), urothelial carcinomas (11), non-small cell lung cancers (12,13), breast cancers (14) and pancreatic cancers (15). In their previous study, Sakata et al (7) suggested that elevated LAT1 expression in prostate cancer core needle biopsy samples may be considered a novel biomarker for high-grade malignancy, but did not clarify the correlation between LAT1 expression and Gleason score, the most commonly used tool for grading the malignancy of prostate cancers.…”
Section: Introductionmentioning
confidence: 99%
“…L-type amino acid transporter 1 (LAT1) is a neutral amino acid transporter and is essential for the transport of large neutral amino acids [6,7]. It has been shown that LAT1 is overexpressed in some malignant tumor cells such as KB human oral epidermoid carcinoma cells [8], esophageal carcinoma [9], Barrett's adenocarcinoma [10], astrocytic tumors [11,12], lung adenocarcinoma [13], oral cancer [14] and osteogenic sarcoma cells [15]. Amino acids are essential for protein synthesis, which is required for critical cell growth and proliferation [16].…”
Section: Introductionmentioning
confidence: 99%